Oh, fishpaste! naku, palpak na naman! textual analysis on the differences in the process oftranslation of the selected episodes of the original and dubbed versions of SpongeBob SquarePants - Dela Fuente, Lawrence Joy Soriano (2012)
"Ever since SpongeBob Squarepants started its airing in 1999, it has become one of the most wanted cartoon shows on television not only in the United States, but also around the world, including the Philippines. It has been on our television for more than ten years, and has been Tagalized along with other canned shows brought here. This brings us to the focus of this research: the differences in the process of translation of the original and dubbed versions of the program SpongeBob SquarePants. This study aims to find the differences in the process of translation of why do these differences exist. Textual analysis was used to analyse the transcriptions of the original and dubbed version of the cartoon show. The study used Josefina Santos' premodernity framework and James Carey's concept of the ritual view of communication in analysing and explaining these differences in translation. Results showed that there are two reasons behind these differences in translation: a) to make the show fit for the Filipino language; and b) to incorporate Filipino culture into the show. Furthermore, it can be suggested that this incorporation of the Filipino culture into the dubbed version is a ritual and this ritual reinforces the premodern ways of our society, which helps maintain the effects of globalization on Philippine media."